DESIGN OF UI/UX APPLICATIONS FOR MOBILE-BASED E-COMMERCE TECH.AN GADGETS USING THE DESIGN METHOD THINKING - Anis Mirza; Melani Dewi Lusita; Desy Diana (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
The use of gadgets is increasingly in demand and increasing every year. Then coupled with the Covid-19 Pandemic where almost all activities are carried out online. The Tech.an application is here so that users can buy electronic goods such as gadgets with clear descriptions or specifications. Tech.an is an e-commerce application that offers main products, namely gadgets with superior features, namely comparisons and COD payments without price limitations. Tech.an is expected to be able to provide information regarding gadget specifications as needed, as well as make it easier for users to purchase gadgets. The user interface design method used in this study is the design thinking method which includes five stages including Emphasize, Define, Ideate, Prototype, and Testing. The test results (testing) on the proposed prototype design also proves that the prototype design meets the eligibility standards. This is done by testing iterations with the final result getting a performance value of 77 and included in the acceptable category.